2020
DOI: 10.1159/000515754
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging Reveals Whole-Brain Microstructural Changes in the P301L Mouse Model of Tauopathy

Abstract: <b><i>Introduction:</i></b> Increased expression of hyperphosphorylated tau and the formation of neurofibrillary tangles are associated with neuronal loss and white matter damage. Using high-resolution ex vivo diffusion tensor imaging (DTI), we investigated microstructural changes in the white and grey matter in the P301L mouse model of human tauopathy at 8.5 months of age. For unbiased computational analysis, we implemented a pipeline for voxel-based analysis (VBA) and atlas-based anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Imaging of GSK-3β also indicated a sex difference in P301L mouse model with difference in tracer uptake only between male P301L and wild-type mice (Knight et al, 2021). In other studies, no behavioral, structural, and metabolic difference was observed in the P301S (Criver.com, 2021) and P301L mice (Ni et al, 2020;Massalimova et al, 2021). Several histology and behavior studies in 3 × Tg mice have also indicated a higher amyloid load in female mice compared to male mice, while no difference in tau level between groups (Hirata-Fukae et al, 2008;Carroll et al, 2010;Yang et al, 2018).…”
Section: Imaging Microglia Activation and Astrocytosismentioning
confidence: 87%
“…Imaging of GSK-3β also indicated a sex difference in P301L mouse model with difference in tracer uptake only between male P301L and wild-type mice (Knight et al, 2021). In other studies, no behavioral, structural, and metabolic difference was observed in the P301S (Criver.com, 2021) and P301L mice (Ni et al, 2020;Massalimova et al, 2021). Several histology and behavior studies in 3 × Tg mice have also indicated a higher amyloid load in female mice compared to male mice, while no difference in tau level between groups (Hirata-Fukae et al, 2008;Carroll et al, 2010;Yang et al, 2018).…”
Section: Imaging Microglia Activation and Astrocytosismentioning
confidence: 87%
“…Magnetic resonance imaging (MRI) provides versatile highresolution structural, functional, and molecular image data with high soft tissue contrast such as T 1 , T 2 anatomical scans, functional connectivity by using fMRI, white matter integrity assessed by diffusion tensor imaging, blood-brain barrier integrity assessed by dynamic contrast enhanced MRI, cerebral perfusion measured by arterial spin labeling sequence, and molecular imaging using contrast agents (Judenhofer et al, 2008;Ni et al, 2019;Ni et al, 2020c;Massalimova et al, 2021). The structural information derived from MRI helps locate specific molecular information provided by OA tomography after registration.…”
Section: Oa/magnetic Resonance Imagingmentioning
confidence: 99%
“…Structural MRI for assessing the neurodegeneration (brain atrophy) in the ATN framework has offered a valuable tool for early and differential diagnosis of AD and for disease staging [ 4 , 6 ]. Moreover, multiplex MRI sequences, such as diffusion tensor imaging (DTI) for white matter integrity assessment, resting-state (rs) functional MRI for functional connectivity analysis [ 7 , 8 ], as well as arterial spin labeling (ASL) for cerebral perfusion measurement, have emerged as potential diagnostic biomarkers for AD.…”
Section: Introductionmentioning
confidence: 99%